Design and Research of Intelligent Building Control System. Issue 4 (January 2021) - He, Yuhan; Du, Yan; Guo, Hongxia; Yang, Jian; Sun, Yanling; Wang, Zhaojun; Li, Congcong; Sun, Kai; Zhang, Meng; Shi, Chunyan; Guo, Liying; Gao, Qun
Abstract: This paper designs and studies an intelligent building control system. The use of object-oriented design principles to design a building automatic control system is an inevitable product of scientific development, a result of the application of modern scientific and technological achievements, and is based on the development of building fieldbus technology. The advantages of the intelligent building control system include: easy design, easy construction, easy to use, easy to manage, and easy to maintain. Through the design and implementation of intelligent building control systems, energy efficiency can be improved, property management efficiency can be improved, technology application thresholds can be reduced, big data value-added services can be added, and energy control can be fully automated and unattended.